Peran Katakese Pastoral dalam Membangun Iman dan Karakter di Era Modern - Jordan Leki; Daniel Labatar; Zakharias Bria (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This research aims to thoroughly examine the role of pastoral catechesis in building faith and character in the modern era. The modern era is characterized by rapid and significant social, cultural, and technological changes. These changes present new challenges to individual faith and character, such as widespread secularism, the strong influence of social media, and the emergence of various ideologies that contradict moral values. The research method used is qualitative with a literature study approach. Data collection was carried out through analysis of literature relevant to the research topic. The literature analyzed includes theology books, scientific articles, Catholic Church documents, and research findings related to religious education and character building. Important findings from this research show that pastoral catechesis plays a crucial role in building individual faith and character in the face of contemporary challenges. Through a systematic process of learning and deepening faith, pastoral catechesis helps individuals to understand the teachings of the Church in depth, develop strong moral values, and build a close relationship with God. Moreover, pastoral catechesis also plays a role in equipping individuals with the knowledge and skills needed to face various challenges in everyday life. This includes the ability to navigate the digital world wisely, analyze information critically, distinguish between right and wrong values, and build healthy relationships with others. Effective and sustainable implementation of pastoral catechesis is key to strengthening the foundation of faith and strong character in today's modern society. This is important for building a community that is faithful, moral, and responsible in facing the challenges of the times, as well as for shaping future generations who are able to be the salt and light of the world.